WANPRESTASI PERJANJIAN KERJA SAMA USAHA COFFEE SHOP SILANG ANTARA PENGELOLA DENGAN PEMILIK MODAL DI KOTA PONTIANAK - NIM. A1012171138, MUHAMMAD REZA ANANDA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The rise of the emergence of coffee shops today cannot be separated from the influence of the lifestyle of a big city. One of the coffee shops favored by many people, especially in the Pontianak city area, is the coffee shop located on Jalan Cendrawasih, namely Silang Coffee, the implementation of the Silang coffee shop business cooperation agreement which where in the implementation of this cooperation agreement contains the capital owners and business managers. The owner of the capital in this case has an obligation to provide funds of Rp. 250,000,000 (two hundred and fifty million rupiah) and provide it as capital for business management and authorize the manager to regulate the financing of the Silang coffee shop, besides that the owner of the capital is entitled to receive profit sharing which is presented as 30% of the net profit . Harry Kalimulya as the owner of the capital and Albian Nobertus Kalimabo as the manager of the coffee shop business entered into a written agreement. However, in reality, business managers do not carry out their obligations as a form of responsibility in accordance with the written agreement with the owner of the capital. The formulation of the problem in this study is: